Identification of transgene integration site and anatomical properties of fluorescence intensity in a EGFP transgenic chicken line. (15th October 2019) - Tsujino, Kaori; Okuzaki, Yuya; Hibino, Nobuyuki; Kawamura, Kazuki; Saito, Seiji; Ozaki, Yumi; Ishishita, Satoshi; Kuroiwa, Atsushi; Iijima, Shinji; Matsuda, Yoichi; Nishijima, Kenichi; Suzuki, Takayuki
Abstract: Transgenic birds are commonly used for time‐lapse imaging and fate mapping studies in developmental biology. When researchers use transgenic birds expressing fluorescent protein, they need to understand the integration site of the transgene in the genome and the intensity of fluorescence in the tissues of interest. In this study, we determined the integration site of the transgene and fluorescence property of developing organs in our transgenic chicken line generated by lentivirus infection. The transgene was localized between exons 3 and 4 of MED27 . Some homozygotes and heterozygotes appeared to be lethal at early embryonic stages. We performed histological analysis of EGFP expression in transgenic embryos at St. 14, 17, and 24 by immunohistochemistry with anti‐GFP antibody on paraffin sections. Next, we cut cryosections and quantified direct EGFP intensity from the transgene in each tissue without performing immunohistochemistry. These results revealed that EGFP intensity in each tissue was unique in developing embryos and changed according to developmental stages. Finally, we demonstrated that EGFP‐expressing cells in a micromass culture with co‐culturing wild‐type cells were clearly distinguishable via live cell imaging. These results provide essential information on the potential of our transgenic line and indicate that these transgenic chicken lines are useful for research associated with developmental biology. Abstract : Images of transgenic and wild‐type chicken embryos at St. 23/24. EGFP protein was expressed ubiquitously in the transgenic embryo.